Tear film profile in patients with active thyroid orbithopathy - Nowak, Mariusz; Marek, Bogdan; Kos-Kudła, Beata; Kajdaniuk, Dariusz; Siemińska, Lucyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Dry eye symptoms and tear film profile were examined in 21 patients with Graves' disease complicated by active thyroid orbitopathy (OT). Dry eye symptoms and clinical tests: break-up time (BUT), Schirmer I, fluorescein and lissamine green staining in OT patients, were comparable with control group. Dry eye symptoms were present in 85% of OT patients compared with 30% in control group. BUT (5.84±3,31sec.) and Schirmer test (11.11±9,14mm) were significantly lower when compared with control group (11.4±3,75sec and 20.5±9,65mm). Lissamin green staining intensity score (3.61±1,74) as well as positive fluorescein staining in OT patients, were significantly higher when compared with control.